2-Hydroxypyridinium p-toluenesulfonate - Yu Jin (Acta Crystallographica Section E, 2012)
In the title molecular salt, C5H6NO+·C7H7O3S−, the cations and anions are connected by N—H...O and O—H...O hydrogen bonds, forming [100] chains.